Molecular and Human In Vivo Study of an Innovative Plant-Derived Multifunctional Peptide Signaling the Collagen and Elastin Pathways and Melanin Production - Carlotta Bollati; Melissa Fanzaga; Lorenza d’Adduzio; Carmen Lammi (Cosmetics, 2025)
Chrono Control Penta is a novel plant derived multifunctional bioactive peptide, which offer a tailored targeted approach to skin health by addressing both pigmentation and aging. Chrono Control Penta inhibits tyrosinase with an IC50 value of 202.8 µM. Additionally, it significantly increased collagen (+87.53%) and elastin (+61.29%) production and secretion (+66.29% and +69.74%, respectively) and decreased the Matrix metalloproteinase-9 (MMP-9) and MMP-2 secretion in aged human dermal fibroblasts, vs. aging condition. At the clinical level, Chrono Control Penta was demonstrated to be already active after 2 weeks, promoting a 9.3% reduction in pigmentation after 6 weeks of use, showing its efficacy in promoting skin complexion. Furthermore, it exhibited significant moisturizing (13.05%), anti-wrinkle (11.55%), and purifying effects (12.45%), as well as firming effects (6.35%), after 6 weeks. The peptide was also well tolerated, with no adverse effects reported in clinical patch tests. This timely study presents novel research on a plant derived peptide, Chrono Control Penta, a significantly contribution to the burgeoning cosmetic peptide market. Our rigorous findings make it a new powerful ingredient, offering a comprehensive solution for skin health, and establishing a strong foundation for future research and application.